Bioprocess development for the production of succinic acid from orange peel waste - Patsalou, Maria; Pateraki, Chrysanthi; Vasquez Christodoulou, Marlen; Drouza, Chryssoula; Koutinas, Michalis (My University, 2016)
A preliminary study has been conducted for the development of a bioprocess targeting the valorization of orange peel waste (OPW). Essential oils and pectin were recovered from OPW through distillation, acid hydrolysis and precipitation with ethanol. Optimal conditions for dilute-acid hydrolysis were investigated via estimation of the sugars released and fermentation. Hydrolysis conditions of 109 o C for 20 min and 116 o C for 10 min using 5 % of dry raw material produced the highest sugar yields at 0.76 and 0.77 (gtotal sugars gdry raw material-1) respectively. In order to test the efficiency of enzyme hydrolysis as a pretreatment method for OPW valorization, cellulase production from T. reesei was investigated, which was maximized following 5 days of cultivation. Furthermore, elemental analysis in hydrolyzates from dilute-acid hydrolysis and a combination of acid and enzyme hydrolysis was performed. The results indicate that during acid/enzyme hydrolysis, high concentrations of Mg2+ and Ca2+ ions are liberated in contrast to dilute-acid hydrolysis. A. succinogenes fermentations of glucose and fructose were performed and the succinic acid yields achieved were 0.66 (gsuccinic acid gglucose-1) and 0.33 (gsuccinic acid gfructose-1) respectively, while galactose was not fermented. Overall, OPW may serve as a promising raw material for simultaneous production of essential oils, pectin and succinic acid.
Keywords: Orange peel waste; Industrial biotechnology; Fermentation; Succinic acid; A. succinogenes; T. reese